Design and synthesis of a focused library of diamino triazines as potential mycobacterium tuberculosis DHFR inhibitors - Lele, Arundhati C.; Raju, Archana; Khambete, Mihir P.; Ray, M. K.; Rajan, M. G. R.; Arkile, Manisha A.; Jadhav, Nandadeep J.; Sarkar, Dhiman; Degani, Mariam S. (ACS Medicinal Chemistry Letters, 2015)
We report design of a series of 2,4-diamino triazines as Mycobacterium tuberculosis (Mtb) dihydrofolate reductase inhibitors. The synthesized compounds were evaluated against Mtb (H(37)Rv and Dormant stage H37Ra), their cytotoxicity was assessed (HepG2 and A549 cell lines), and selectivity toward Mtb was evaluated by testing against other bacterial strains. Some derivatives showed promising activity along with low cytotoxicity. The most potent compound in the whole cell assay (MIC 0.325 mu M against H(37)Rv) showed selectivity in the enzyme assay and exhibited synergy with second line anti-TB agent p-amino salicylic acid. This study therefore provides promising molecules for further development as antituberculosis DHFR inhibitors.
Keywords: Diamino triazine; dihydrofolate reductase; enzyme assay; molecular modeling; Mycobacterium tuberculosis; selectivity; synergy

Rational drug design, synthesis and biological evaluation of dihydrofolate reductase inhibitors as antituberculosis agents - Tawari, Nilesh R.; Bag, Seema; Raju, Archana; Lele, Arundhati C.; Bairwa, Ranjeet; Ray, Mukti Kanta; Rajan, M. G. R.; Nawale, Laxman U.; Sarkar, Dhiman; Degani, Mariam S. (Future Medicinal Chemistry, 2015)
Background: A series of 2,4-diamino-s-triazines was designed, with potential for activity against Mycobacterium tuberculosis (Mtb) dihydrofolate reductase enzyme, on the basis of virtual screening results and structure-based drug design. Results: The compounds were evaluated against Mtb (H(37)Rv) and their cytotoxicity was assessed using VERO cell lines. Of particular note, two compounds were found to have the most promising antituberculosis activity (6b minimum inhibitory concentration: 1.76 mu M and 6i minimum inhibitory concentration: 1.57 mu M) along with low cytotoxicity (CC50 : > 300 mu M). The enzyme assay results of these two indicated significant inhibition of Mtb dihydrofolate reductase along with selectivity. Selected derivatives were tested against dormant tubercle bacilli in vivo and ex vivo indicating potential inhibition. Conclusion: This study provides promising antituberculosis dihydrofolate reductase inhibitors that can act as potential leads for further development.

Rational design of coumarin derivatives as antituberculosis agents - Mali, Hemlata M.; Sabale, Sandip S.; Degani, Mariam S.; Borkute, Rachana; Choudhari, Amit S.; Sarkar, Dhiman; Krishna, Vagolu Siva; Sriram, Dharmarajan (Future Medicinal Chemistry, 2018)
A series of coumarin derivatives was designed as potential antituberculosis agents. Results: The compounds were screened against active and dormant Mycobacterium tuberculosis (Mtb). Compounds 3k and 3n were found to have the most promising activity against replicating MtbH37Rv exhibiting minimum inhibitory concentration of 4.63 and 9.75 mu M respectively. The compounds were also effective against dormant MtbH37Rv exhibiting more potency than the standard drugs, isoniazid and rifampicin. The compounds were found to be non-cytotoxic against human cell lines. Conclusion: This study provides promising antituberculosis agents that are effective against replicating as well as dormant Mtb and can thus act as potential leads for further development.